Manufacturing method of stainless steel sheet for fuel cell separator
A two-step surface treatment process on stainless steel plates with controlled grain size and annealing addresses safety and cost issues in manufacturing fuel cell separators, achieving low contact resistance and efficient mass production.
Patent Information
- Application Number
- JP2022095909
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-06-14
- Publication Date
- 2025-01-06
- Estimated Expiration
- 2042-06-14
Smart Images

Figure 0007608395000004 
Figure 0007608395000005 
Figure 0007608395000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for manufacturing a stainless steel sheet for use as a separator in a fuel cell. [Background technology]
[0002] In recent years, from the perspective of protecting the global environment, there has been progress in the development of fuel cells, which have excellent power generation efficiency and do not emit carbon dioxide. These fuel cells generate electricity through an electrochemical reaction between hydrogen and oxygen. The basic structure of a fuel cell is like a sandwich, and is made up of an electrolyte membrane (ion exchange membrane), two electrodes (fuel electrode and air electrode), diffusion layers for O2 (air) and H2, and two separators (bipolar plates). Depending on the type of electrolyte membrane used, fuel cells are classified into phosphoric acid fuel cells, molten carbonate fuel cells, solid oxide fuel cells, alkaline fuel cells, and polymer electrolyte fuel cells (PEFCs; proton-exchange membrane fuel cells or polymer electrolyte fuel cells), and development of each type is currently underway.
[0003] Of these fuel cells, polymer electrolyte fuel cells in particular are expected to be used as on-board power sources for electric vehicles, stationary generators for home or commercial use, and small portable generators.
[0004] A polymer electrolyte fuel cell extracts electricity from hydrogen and oxygen through a polymer membrane. In a polymer electrolyte fuel cell, a membrane-electrode assembly is sandwiched between a gas diffusion layer (e.g., carbon paper) and a separator to form a single component (a so-called single cell). An electromotive force is generated between the fuel electrode side separator and the air electrode side separator. The membrane-electrode assembly is called an MEA (Membrane-Electrode Assembly), and is an integrated structure of a polymer membrane and an electrode material such as carbon black carrying a platinum catalyst on the front and back surfaces of the membrane. The thickness of the membrane-electrode assembly is several tens of μm to several hundreds of μm. In many cases, the gas diffusion layer is integrated with the membrane-electrode assembly.
[0005] Moreover, when a solid polymer electrolyte fuel cell is put to practical use, it is common to connect several tens to several hundreds of such single cells in series to form a fuel cell stack. (a) Partition wall separating unit cells In addition to its role as (b) A conductor that carries the generated electrons; (c) an air flow path through which oxygen (air) flows, and a hydrogen flow path through which hydrogen flows; (d) An exhaust passage for discharging the water and gas produced (combines air and hydrogen flow passages) Since they are required to function as such, they need to have excellent durability and electrical conductivity.
[0006] Of these, durability is determined by corrosion resistance, because when the separator corrodes and metal ions are eluted, the proton conductivity of the polymer membrane (electrolyte membrane) decreases, resulting in a decrease in power generation characteristics.
[0007] Regarding electrical conductivity, it is desirable that the contact resistance between the separator and the gas diffusion layer be as low as possible. This is because if the contact resistance between the separator and the gas diffusion layer increases, the power generation efficiency of the polymer electrolyte fuel cell decreases. In other words, the smaller the contact resistance between the separator and the gas diffusion layer, the better the power generation characteristics.
[0008] To date, polymer electrolyte fuel cells using graphite as a separator have been put to practical use. The graphite separator has the advantages of being relatively low in contact resistance and not corroding. However, graphite separators have the disadvantage of being easily damaged by impact. In addition, graphite separators are difficult to miniaturize, and have the disadvantage of high processing costs for forming air and hydrogen channels. These disadvantages of graphite separators are preventing the widespread use of polymer electrolyte fuel cells.
[0009] Therefore, attempts have been made to use metallic materials instead of graphite as separator materials. In particular, from the viewpoint of improving durability, various studies have been made toward the practical use of separators made of stainless steel, titanium, titanium alloys, etc.
[0010] For example, Patent Document 1 discloses a technique for using metals that easily form a passive film, such as stainless steel and titanium alloys, as separators. However, the technique disclosed in Patent Document 1 invites an increase in contact resistance due to the formation of a passive film. As a result, power generation efficiency decreases. Thus, the metal material disclosed in Patent Document 1 has problems such as a higher contact resistance than graphite materials.
[0011] In order to reduce the contact resistance, for example, Patent Document 2 discloses the following: "A ferritic stainless steel with excellent corrosion resistance and electrical conductivity, characterized in that it contains, by mass%, 0.001-0.05% C, 0.001-0.5% Si, 0.001-1.0% Mn, 0.001-0.5% Al, 0.001-0.05% N, 17-23% Cr, 0.1% or less Mo, with the remainder being Fe and unavoidable impurities, and has a coating on its surface obtained by immersing in an immersion treatment solution mainly composed of hydrofluoric acid or hydrofluoric and nitric acid, the relationship of which, when the hydrofluoric acid concentration is expressed as [HF] and the nitric acid concentration is expressed as [HNO3], being expressed as the formula: [HF] ≧ [HNO3] … [1]." has been disclosed.
[0012] In addition, Patent Document 3 states: "A method for producing stainless steel for fuel cell separators, comprising electrolytic treatment of stainless steel containing 16 mass% or more of Cr, followed by immersion treatment in a solution containing fluorine." has been disclosed.
[0013] Furthermore, Patent Document 4 states: "A stainless steel containing, by mass%, C: 0.03% or less, Si: 1.0% or less, Mn: 1.0% or less, S: 0.01% or less, P: 0.05% or less, Al: 0.20% or less, N: 0.03% or less, Cr: 16 to 40%, and one or more of Ni: 20% or less, Cu: 0.6% or less, and Mo: 2.5% or less, with the balance being Fe and unavoidable impurities, A stainless steel for fuel cell separators, characterized in that when the surface of the stainless steel is measured by photoelectron spectroscopy, F is detected and non-metallic form (Cr+Fe) / metallic form (Cr+Fe)≧3.0 is satisfied. has been disclosed.
[0014] In addition, Patent Document 5 states: "A stainless steel containing 16 to 40 mass% Cr, The stainless steel for fuel cell separators has low surface contact resistance, characterized in that the surface of the stainless steel has a fine uneven structure that accounts for 50% or more of its surface area. has been disclosed. [Prior art documents] [Patent documents]
[0015] [Patent Document 1] Japanese Patent Application Publication No. 8-180883 [Patent Document 2] Patent No. 5768641 [Patent Document 3] JP 2013-93299 A [Patent Document 4] Patent No. 5218612 [Patent Document 5] International Publication No. 2013 / 080533 [Patent Document 6] International Publication No. 2019 / 082591 Summary of the Invention [Problem to be solved by the invention]
[0016] However, when the stainless steel sheets disclosed in Patent Documents 2 to 5 are immersed in a treatment solution containing hydrofluoric acid as an etching treatment, Fe ions and the like are eluted from the steel sheet, which is the material to be treated. This reduces the etching ability of hydrofluoric acid, and the desired effect of reducing contact resistance may not be stably obtained. In addition, the treatment solution containing hydrofluoric acid is chemically very active, which causes safety problems during the treatment. In addition, safety problems also occur in the treatment of waste liquid discharged after the treatment.
[0017] Therefore, the inventors have conducted extensive research to solve the above problems, and previously reported in Patent Document 6: "Prepare the stainless steel plate as the material, Next, the oxide film on the surface of the stainless steel plate is removed, Next, the stainless steel plate is subjected to an electrolytic etching treatment in the active region of the stainless steel plate. disclosed.
[0018] The technology of Patent Document 6 mentioned above makes it possible to manufacture stainless steel plates for fuel cell separators, which provide low contact resistance, in a safer and more stable manner without using a treatment solution containing hydrofluoric acid.
[0019] However, the technique of Patent Document 6 requires electrolytic etching, which requires a huge electrolytic device for mass production, resulting in high facility costs. In addition, when electrolytic etching is performed after pressing a stainless steel plate, electrodes must be attached to the pressed product, which is time-consuming.
[0020] The present invention was developed in consideration of the above-mentioned current situation, and has an object to provide a method for manufacturing stainless steel sheets for fuel cell separators, which can produce stainless steel sheets for fuel cell separators having low contact resistance in a manner that is extremely advantageous not only in terms of safety but also in terms of mass productivity. [Means for solving the problem]
[0021] The inventors conducted extensive research to solve the above problems and obtained the following findings. (1) First, from the viewpoint of improving mass productivity, the inventors performed various etching treatments on various stainless steel sheets and measured the contact resistance of the stainless steel sheets after the treatments. Specifically, instead of the electrolytic etching treatment as in Patent Document 6, the inventors performed an etching treatment in which the stainless steel sheets were immersed in various treatment solutions, and measured the contact resistance of the stainless steel sheets after the treatments.
[0022] (2) As a result, the inventors discovered that a highly effective reduction in contact resistance can be obtained in a stainless steel sheet that simultaneously satisfies the following (a) to (c): (a) Parameter Sa defined in ISO 25178: 0.15 μm or more and 0.50 μm or less, preferably 0.20 μm or more and 0.48 μm or less (b) Parameter Ssk specified in ISO 25178: greater than 0 (c) [Other than metal form (Cr+Fe)] / [Metal form (Cr+Fe)]: 8.0 or less Here, the parameter Sa defined in ISO 25178 is a type of surface roughness parameter and represents the arithmetic mean height. The arithmetic mean height is the average of the absolute values of the differences in height of each point relative to the average plane of the surface, and is a parameter that is commonly used when evaluating surface roughness. The parameter Ssk (skewness) defined in ISO 25178 is a type of surface roughness parameter that indicates the symmetry of the height distribution. As shown in Figure 2, when Ssk (skewness) is a positive value (greater than 0), it indicates that the tips (tops) of the convex parts (peaks) are sharp and the tips (bottoms) of the concave parts (valleys) are wide (approaching flat). On the other hand, when Ssk is a negative value (less than 0), it indicates that the tips (tops) of the convex parts (peaks) are wide (approaching flat) and the tips (bottoms) of the concave parts (valleys) are sharp. [Other than metallic form (Cr+Fe)] / [Metallic form (Cr+Fe)] is the ratio of the sum of Cr and Fe present in a form other than metal to the sum of Cr and Fe present in a form of metal on the steel sheet surface. Also, [Metallic form (Cr+Fe)] and [Other than metallic form (Cr+Fe)] are the sum of the atomic concentrations of Cr and Fe present in a form of metal and the sum of the atomic concentrations of Cr and Fe present in a form other than metal, respectively, measured when the steel sheet surface is analyzed by X-ray photoelectron spectroscopy.
[0023] (3) Furthermore, the inventors have determined that in order to obtain a stainless steel sheet that simultaneously satisfies the above (a) to (c), (d) As a first surface treatment, a surface treatment is performed using an acidic aqueous solution containing hydrogen peroxide, copper ions and halide ions as a treatment liquid, and the treatment temperature and treatment time are set to 30 to 50°C and 40 to 120 seconds, respectively; (e) After the first surface treatment, a second surface treatment is performed using an aqueous solution containing nitric acid at a treatment temperature of 30 to 60° C. for a treatment time of 5 to 120 seconds. It has been found that this makes it possible to obtain a sufficient effect of reducing the contact resistance without carrying out electrolytic etching or etching with hydrofluoric acid.
[0024] (4) That is, the inventors used a laser microscope to check the surface properties of various stainless steel sheets obtained after the above-mentioned various surface treatments (etching treatments in which the stainless steel sheet is immersed in various treatment solutions), and found that the surface of a stainless steel sheet with low contact resistance (hereinafter also referred to as the stainless steel sheet of the present application) has irregularities with convex parts having sharp tip shapes as shown in Figure 1.
[0025] (5) Based on this finding, the inventors further investigated the matter. By simultaneously satisfying the above requirements (a) to (c), an extremely excellent effect of reducing contact resistance can be obtained. In order to obtain the surface properties (a) and (b) described above, it is effective to carry out the first surface treatment under the condition (d) described above; and In order to obtain the above (c) [non-metallic form (Cr+Fe)] / [metallic form (Cr+Fe)], it is effective to carry out the second surface treatment under the above (e) conditions; They discovered that:
[0026] (6) The inventors consider the mechanism by which an extremely excellent effect of reducing contact resistance can be obtained by simultaneously satisfying the above (a) to (c) as follows. That is, the separator of the fuel cell contacts the gas diffusion layer made of carbon paper, carbon cloth, or the like under a predetermined load. In the stainless steel plate obtained by the conventional electrolytic etching process or hydrofluoric acid etching process, many fine irregularities are formed on the surface of the steel plate. The fine irregularities increase the contact area between the separator (stainless steel plate) and the gas diffusion layer. As a result, the contact resistance is reduced. On the other hand, as described above, the surface of the stainless steel plate of the present application has irregularities with sharp tips of the protrusions. Therefore, as shown in FIG. 3, when the separator (stainless steel plate) and the gas diffusion layer contact each other, the tips of the protrusions formed on the surface of the stainless steel plate of the present application pierce the carbon fibers of the gas diffusion layer. Then, the part (the part where the tip of the protrusion pierces the carbon fiber of the gas diffusion layer) becomes a current path, and the contact resistance is reduced. In other words, the inventors believe that the mechanism by which the contact resistance reduction effect is obtained in the stainless steel plate of the present application is different from the mechanism by which the contact resistance reduction effect is obtained in the stainless steel plate obtained by the conventional electrolytic etching process or hydrofluoric acid etching process. In fact, the inventors have performed conventional electrolytic etching and etching using hydrofluoric acid. When the surface property data of the stainless steel sheet obtained after the treatment was measured, it was found that Sa was less than 0.15 μm or Ssk was a negative value (less than 0), which was clearly different from the surface property of the stainless steel sheet of the present application.
[0027] (7) As described above, the surface of the stainless steel plate of the present application has projections with sharp tips. Therefore, when the separator (stainless steel plate) and the gas diffusion layer come into contact with each other, the tips of the projections formed on the surface of the stainless steel plate of the present application pierce the carbon fibers of the gas diffusion layer. Then, the part (where the tip of the projection pierces the carbon fibers of the gas diffusion layer) becomes a current path, and the contact resistance is reduced. However, during etching in the first surface treatment, a large amount of smut (a mixture mainly composed of C, N, S, O, Fe, Cr, Ni, and Cu) is generated as the steel plate dissolves, and these are attached to the steel plate surface. Since smut has high electrical resistance, the contact resistance of the steel plate as it is after the first surface treatment (etching treatment) is increased due to the influence of such smut. In this regard, by using an aqueous solution containing nitric acid as the treatment liquid in the second surface treatment, it becomes possible to particularly effectively remove smut attached to the steel plate surface. In addition, the amount of smut on the steel sheet surface is correlated with [non-metallic form (Cr+Fe)] / [metallic form (Cr+Fe)], and it can be said that the lower the [non-metallic form (Cr+Fe)] / [metallic form (Cr+Fe)], the more adequately the smut has been removed. Therefore, by controlling the [non-metallic form (Cr+Fe)] / [metallic form (Cr+Fe)] ratio to 8.0 or less, the contact resistance can be further reduced, resulting in an extremely excellent reduction in contact resistance.
[0028] (8) Furthermore, the inventors investigated the effect of the average crystal grain size of the stainless steel sheet on the dissolution behavior during the first surface treatment. As a result, it was found that it is preferable to set the average crystal grain size of the stainless steel sheet to be treated in the first surface treatment (i.e., the stainless steel sheet to be used as the base material) to be 10 μm or more and 40 μm or less, and that this makes it possible to obtain the above surface properties (a) and (b) with a smaller amount of dissolution.
[0029] The present invention was completed based on the above findings and after further investigation.
[0030] That is, the gist and configuration of the present invention are as follows. 1. A first surface treatment step of subjecting a base stainless steel sheet to a first surface treatment; a second surface treatment step of subjecting the base stainless steel plate to a second surface treatment after the first surface treatment step; In the first surface treatment, The treatment liquid is an acidic aqueous solution containing 0.1 to 5.0 mass% hydrogen peroxide, 1.0 to 10.0 mass% copper ions, and 5.0 to 20.0 mass% halide ions and having a pH of 1.0 or less; and Processing temperature: 30~50℃ and Processing time: 40 to 120 seconds and In the second surface treatment, The treatment liquid is an aqueous solution containing nitric acid, Processing temperature: 30~60℃ and Processing time: 5 to 120 seconds This is a method for manufacturing stainless steel sheets for fuel cell separators.
[0031] 2. The method for producing a stainless steel sheet for a fuel cell separator as described in 1 above, wherein the average crystal grain size of the base stainless steel sheet is 10 μm or more and 40 μm or less.
[0032] 3. A method for producing a stainless steel sheet for a separator of a fuel cell according to the above item 2, comprising the steps of: The method further comprises: a hot rolling step of hot rolling the steel slab into a hot rolled sheet; A cold rolling process in which the hot rolled sheet is cold rolled to obtain a cold rolled sheet; A cold-rolled sheet annealing process for subjecting the cold-rolled sheet to cold-rolled sheet annealing; The base stainless steel plate is an austenitic stainless steel plate, and In the final annealing, which is the final annealing of the cold-rolled sheet annealing, Final annealing temperature: 1050~1250℃ and Finish annealing time: 20 to 90 seconds This is a method for manufacturing stainless steel sheets for fuel cell separators.
[0033] 4. A method for producing a stainless steel sheet for a separator of a fuel cell according to the above item 2, comprising the steps of: The method further comprises: a hot rolling step of hot rolling the steel slab into a hot rolled sheet; A cold rolling process in which the hot rolled sheet is cold rolled to obtain a cold rolled sheet; A cold-rolled sheet annealing process for subjecting the cold-rolled sheet to cold-rolled sheet annealing; The base stainless steel plate is a ferritic stainless steel plate, and In the final annealing, which is the final annealing of the cold-rolled sheet annealing, Final annealing temperature: 750~1050℃ and Finish annealing time: 20 to 90 seconds This is a method for manufacturing stainless steel sheets for fuel cell separators. Effect of the Invention
[0034] According to the present invention, stainless steel plates for fuel cell separators having low contact resistance can be manufactured without electrolytic etching (electrochemical dissolution treatment) or etching with hydrofluoric acid, which is extremely advantageous not only in terms of safety but also in terms of mass productivity. [Brief description of the drawings]
[0035] [Figure 1] 1 is a photograph taken with a laser microscope showing an example of the surface condition of a stainless steel plate for a fuel cell separator manufactured by a manufacturing method for a stainless steel plate for a fuel cell separator according to one embodiment of the present invention. [Diagram 2] 1 is a schematic diagram (cross-sectional view) showing the surface state when Ssk (skewness) is a positive value (greater than 0) and a negative value (less than 0). [Diagram 3] FIG. 2 is a schematic diagram (cross-sectional view) showing a contact state when a stainless steel plate (separator) for a fuel cell separator comes into contact with carbon fibers of a gas diffusion layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0036] (1) Manufacturing method of stainless steel sheet for fuel cell separator A method for producing a stainless steel sheet for a fuel cell separator according to one embodiment of the present invention will now be described.
[0037] [Preparation of stainless steel plate material] A stainless steel sheet to be used as a base material (hereinafter also referred to as a base stainless steel sheet) is prepared. The method for preparing the base stainless steel sheet is not particularly limited, and for example, a commercially available stainless steel sheet may be processed to a predetermined size to prepare the base stainless steel sheet. Alternatively, a base stainless steel sheet having the component composition described below may be prepared as follows. That is, for example, a steel slab having a composition described later is hot-rolled to form a hot-rolled sheet, which is annealed and pickled as necessary, and then cold-rolled to form a cold-rolled sheet of a desired thickness, which is annealed as necessary, to prepare a stainless steel sheet having the composition described above. The conditions for hot rolling, cold rolling, hot-rolled sheet annealing, pickling, cold-rolled sheet annealing, etc. are not particularly limited, and may be in accordance with conventional methods. In addition, pickling and skin pass may be performed after cold-rolled sheet annealing. In addition, the cold-rolled sheet annealing may be bright annealing.
[0038] The stainless steel sheet material may be any of a ferritic stainless steel sheet, an austenitic stainless steel sheet, and a ferritic-austenitic two-phase stainless steel sheet, but from the viewpoint of workability, an austenitic stainless steel sheet is preferable. Here, the structure of the ferritic stainless steel sheet may be a single-phase structure of the ferritic phase, and may contain precipitates of 1% or less in volume fraction as the remainder other than the ferritic phase. The structure of the austenitic stainless steel sheet may be a single-phase structure of the austenitic phase, and may contain precipitates of 1% or less in volume fraction as the remainder other than the austenitic phase. The structure of the ferritic-austenitic two-phase stainless steel sheet (hereinafter also referred to as a two-phase stainless steel sheet) may be composed of a ferritic phase and an austenitic phase, and may contain precipitates of 1% or less in volume fraction as the remainder other than the ferritic phase and the austenitic phase. The above-mentioned precipitates may be, for example, one or more selected from the group consisting of intermetallic compounds, carbides, nitrides, and sulfides. The identification of each phase may be carried out according to a conventional method.
[0039] From the viewpoint of reducing the size and weight of the fuel cell stack, the thickness of the stainless steel material plate is preferably 0.30 mm or less, and more preferably 0.15 mm or less. On the other hand, in order to ensure the strength and durability of the separator, the thickness of the stainless steel material plate is preferably 0.03 mm or more, and more preferably 0.05 mm or more.
[0040] In addition, the average crystal grain size of the base stainless steel sheet is preferably 10 μm or more and 40 μm or less. That is, an as-rolled stainless steel sheet that has not been annealed has a uniform processed structure that is not recrystallized. When such an as-rolled stainless steel sheet is subjected to the first surface treatment described later, dissolution proceeds uniformly in the stainless steel sheet. On the other hand, in a stainless steel sheet obtained by annealing an as-rolled stainless steel sheet (hereinafter also referred to as an annealed stainless steel sheet), the boundaries between recrystallized crystal grains (hereinafter also referred to as grain boundaries) become the starting points of dissolution. Therefore, when such an annealed stainless steel sheet is subjected to the first surface treatment described later, dissolution proceeds non-uniformly in the stainless steel sheet. When dissolution of the stainless steel sheet proceeds non-uniformly in the first surface treatment, unevenness in the surface of the stainless steel sheet is more likely to occur at a stage where the amount of dissolution is smaller than when dissolution proceeds uniformly.
[0041] Based on the above findings, the inventors conducted extensive research and found that by appropriately controlling the grain size of the stainless steel sheet material, specifically by controlling the average grain size to within the range of 10 μm to 40 μm, the desired surface properties (Sa and Ssk) of the final stainless steel sheet product can be obtained with a smaller amount of dissolution. If the amount of dissolution can be reduced, many advantages can be obtained, such as a shorter treatment time (immersion time) in the first surface treatment, a lower treatment temperature, a reduced amount of treatment liquid used, a reduced cost of treating used treatment liquid, and an improved product yield.
[0042] Here, if the average crystal grain size is 10 μm or more, a sufficient amount of defects accumulates at the crystal grain boundaries, the difference in dissolution characteristics between the crystal grain boundaries and the crystal grains becomes large, and the above-mentioned effect of reducing the amount of dissolution is preferably obtained. On the other hand, if the average crystal grain size exceeds 40 μm, the amount of crystal grain boundaries per unit area decreases, and the above-mentioned effect of reducing the amount of dissolution decreases. Therefore, it is preferable that the average crystal grain size is 10 μm or more and 40 μm or less.
[0043] Additionally, the average crystal grain size of the raw stainless steel sheet is determined by EBSD (electron backscatter diffraction) analysis. That is, the steel plate is embedded in resin and the surface is polished so that the cross section parallel to the rolling direction of the steel plate to be measured is exposed. Then, EBSD analysis is performed and the average crystal grain size is calculated based on the area fraction method. The field area for EBSD analysis is 0.025 mm 2 It is desirable to ensure that the viewing field width is 0.25 mm or more. For example, in the case of a steel plate with a thickness of 0.10 mm, it is desirable that the viewing field width is 0.25 mm or more. Other conditions may be as per usual. The grain size of each crystal grain is calculated by calculating the circle equivalent diameter from the area of each crystal grain obtained by the area fraction method.
[0044] In addition, from the viewpoint of controlling the average crystal grain size of the base stainless steel sheet within the above range, it is preferable to appropriately control the conditions of the finish annealing, which is the final annealing step in the annealing of cold-rolled sheet, in particular the finish annealing temperature and finish annealing time.
[0045] Specifically, when the base stainless steel plate is an austenitic stainless steel plate, a hot rolling step of hot rolling the steel slab into a hot rolled sheet; A cold rolling process in which the hot rolled sheet is cold rolled to obtain a cold rolled sheet; A cold-rolled sheet annealing process for subjecting the cold-rolled sheet to cold-rolled sheet annealing; In the final annealing, which is the final annealing of the cold-rolled sheet annealing, Final annealing temperature: 1050~1250℃ and Finish annealing time: 20 to 90 seconds It is preferable that: In this case, the final annealing temperature is preferably 1100° C. or higher. The final annealing temperature is preferably 1200° C. or lower. The final annealing time is preferably 30 seconds or longer. The final annealing time is preferably 60 seconds or shorter.
[0046] In addition, if the base stainless steel plate is a ferritic stainless steel plate, a hot rolling step of hot rolling the steel slab into a hot rolled sheet; A cold rolling process in which the hot rolled sheet is cold rolled to obtain a cold rolled sheet; A cold-rolled sheet annealing process for subjecting the cold-rolled sheet to cold-rolled sheet annealing; In the final annealing, which is the final annealing of the cold-rolled sheet annealing, Final annealing temperature: 750~1050℃ and Finish annealing time: 20 to 90 seconds It is preferable that: In this case, the final annealing temperature is preferably 800° C. or higher. The final annealing temperature is preferably 1000° C. or lower. The final annealing time is preferably 30 seconds or longer. The final annealing time is preferably 60 seconds or shorter.
[0047] The conditions of the final annealing other than the above are not particularly limited and may be the same as those of the conventional method. For example, the atmosphere of the final annealing is preferably a non-oxidizing atmosphere (e.g., a mixed atmosphere of H2 and N2 (volume ratio of H2:N2=75:25, dew point: -50°C)).
[0048] In either case, the hot-rolled sheet may be subjected to hot-rolled sheet annealing and pickling as necessary. The conditions of hot rolling, cold rolling, hot-rolled sheet annealing, pickling, cold-rolled sheet annealing (intermediate annealing) other than finish annealing are not particularly limited, and may be in accordance with conventional methods. However, it is preferable to set the reduction ratio between the final intermediate annealing and finish rolling to 50% or more. After cold-rolled sheet annealing, pickling and skin pass may be performed. When cold-rolled sheet annealing is performed in one step, the first annealing corresponds to the finish annealing.
[0049] [First surface treatment (etching)] The stainless steel sheet material prepared as described above is subjected to a surface treatment (etching treatment) as a first surface treatment, using an acidic aqueous solution containing 0.1-5.0 mass% hydrogen peroxide, 1.0-10.0 mass% copper ions, and 5.0-20.0 mass% halide ions, with a pH of 1.0 or less, at a treatment temperature of 30-50°C and a treatment time of 40-120 seconds. By performing the etching treatment according to the above conditions, it becomes possible to precisely control the amount of the stainless steel sheet dissolved, and in turn to control the shape of the uneven structure formed on the steel sheet surface as described above. The etching treatment conditions are described below. The amount of dissolution of the stainless steel sheet in the etching process varies depending on the type and temperature of the processing solution used in the etching process and the processing time, among other things, so it is important to appropriately control these conditions in order to obtain the desired surface properties (for example, the surface of the steel sheet has parts that dissolve easily and parts that dissolve less easily, so that unevenness is formed on the steel sheet surface by the etching process. However, if the amount of dissolution of the stainless steel sheet becomes excessively large, etching will also progress in the parts of the steel sheet surface that dissolve less easily, and the convex parts (mountains) will become gentler, resulting in a negative Ssk value.) First, the suitable concentrations of each component contained in the above processing solution will be explained.
[0050] Hydrogen peroxide: 0.1 to 5.0% by mass If the hydrogen peroxide concentration is less than 0.1 mass%, the ability to remove copper-containing products precipitated on the steel sheet surface decreases, making it impossible to perform continuous etching. On the other hand, if the hydrogen peroxide concentration exceeds 5.0 mass%, the effect becomes saturated. Therefore, the hydrogen peroxide concentration is set to 0.1 to 5.0 mass%.
[0051] Copper ions: 1.0 to 10.0% by mass If the copper ion concentration is less than 1.0 mass%, the etching power decreases, making it impossible to form a desired uneven structure on the steel sheet surface. On the other hand, if the copper ion concentration exceeds 10.0 mass%, the amount of products adhering to the steel sheet surface increases, and smut cannot be sufficiently removed even if the second surface treatment in the next step is performed. Therefore, the copper ion concentration is set to 1.0 to 10.0 mass%. The copper ion concentration is preferably 2.0 mass% or more, and more preferably 5.0 mass% or more.
[0052] Halide ions: 5.0 to 20.0 mass% If the concentration of halide ions is less than 5.0% by mass, the passive film present on the surface of the stainless steel sheet cannot be sufficiently destroyed, and etching cannot proceed sufficiently. On the other hand, if the concentration of halide ions exceeds 20.0% by mass, local pitting corrosion is accelerated, and holes may be formed in the steel sheet. Therefore, the concentration of halide ions is set to 5.0 to 20.0% by mass. The concentration of halide ions is preferably 10.0% by mass or more. In addition, the concentration of halide ions is preferably 15.0% by mass or less. The type of halide ion source is not particularly limited, but for example, hydrogen halide or an alkali metal halide is preferable, and hydrochloric acid or sodium chloride is more preferable. Note that the halide ions referred to here mean chloride ions, bromide ions, iodide ions, and astatine ions, and do not include fluoride ions. In addition, chloride ions are preferable as the halide ions.
[0053] pH: 1.0 or less If the pH of the treatment liquid exceeds 1.0, the etching power decreases, and it becomes impossible to form the desired uneven structure on the steel sheet surface. Therefore, the pH of the treatment liquid is set to 1.0 or less. The pH of the treatment liquid is preferably low, more preferably 0.1 or less.
[0054] The above aqueous solution can be prepared, for example, by stirring an aqueous hydrogen peroxide solution, a copper compound capable of supplying copper ions, a halide component capable of supplying halide ions, and water until the mixture is homogeneous. The above aqueous solution may contain unavoidable impurities, but the fluoride ions are controlled to 0.1% by mass or less, preferably 0.01% by mass or less.
[0055] Processing temperature (temperature of processing solution): 30~50℃ If the treatment temperature falls below 30°C, the etching power decreases, leading to an increase in treatment time. On the other hand, if the treatment temperature exceeds 50°C, the stability of the treatment solution decreases. For this reason, the treatment temperature is set to 30°C to 50°C. In particular, when the average crystal grain size of the base stainless steel sheet is 10 μm or more and 40 μm or less, the desired surface properties (Sa and Ssk) can be obtained in the final stainless steel sheet product with a smaller amount of dissolution, so it is even more preferable to set the treatment temperature to 40°C or less.
[0056] Processing time: 40 to 120 seconds If the treatment time is less than 40 seconds, a sufficient amount of etching cannot be obtained. On the other hand, if the treatment time exceeds 120 seconds, it becomes impossible to form a predetermined uneven structure on the steel sheet surface. In addition, productivity decreases. Therefore, the treatment time is set to 40 to 120 seconds. Since the amount of etching varies depending on the type of stainless steel, it is more preferable to adjust the treatment time within the range of 40 to 120 seconds depending on the type of steel. In particular, when the average crystal grain size of the base stainless steel sheet is 10 μm or more and 40 μm or less, the desired surface properties (Sa and Ssk) can be obtained in the stainless steel sheet that becomes the final product with a smaller amount of dissolution, so it is more preferable to set the treatment time to 60 seconds or less.
[0057] Also, it is preferable that the reduction in thickness of the base stainless steel sheet is small. For example, when the average crystal grain size of the base stainless steel sheet is 10 μm or more and 40 μm or less, it is possible to reduce the reduction in thickness of the base stainless steel sheet due to the surface treatment to about 10 to 20 μm. The reduction in thickness of the base stainless steel sheet can be determined by subtracting the thickness of the stainless steel sheet for the separator of the fuel cell that is finally manufactured from the thickness of the base stainless steel sheet.
[0058] Other conditions than those mentioned above are not particularly limited, and may be performed according to conventional methods. The first surface treatment may be performed by contacting the base stainless steel sheet with the treatment liquid, and may be performed, for example, by immersing the base stainless steel sheet in the treatment liquid, or by dripping or spraying the treatment liquid onto the base stainless steel sheet. From the viewpoint of productivity, the mode in which the base stainless steel sheet is immersed in the treatment liquid is preferable. The treatment time is the contact time between the base stainless steel sheet and the treatment liquid, and in the mode in which the base stainless steel sheet is immersed in the treatment liquid, the treatment time is the immersion time in the treatment liquid. In addition to continuously treating the steel strip, the first surface treatment may be performed after processing into a separator shape. The explanations regarding the modes in this paragraph are the same for the second surface treatment and preliminary surface treatment described later, and therefore the explanations regarding the second surface treatment and preliminary surface treatment described later will be omitted.
[0059] [Second surface treatment (smut removal)] After the first surface treatment, the stainless steel sheet is further subjected to a second surface treatment in which an aqueous solution containing nitric acid is used as the treatment liquid, and the treatment temperature and treatment time are 30 to 60°C and 5 to 120 seconds, respectively.
[0060] That is, after the first surface treatment, smut (a mixture whose main constituent elements are C, N, S, O, Fe, Cr, Ni, and Cu, and has high electrical resistance) is generated on the surface of the stainless steel sheet, and if this remains, it may cause an increase in contact resistance even if the desired uneven structure is obtained. In this regard, by performing a surface treatment in a solution containing nitric acid after the first surface treatment, the above-mentioned smut is removed, and the effect of reducing contact resistance is obtained.
[0061] Here, the solution containing nitric acid may be, for example, an aqueous solution of nitric acid. When an aqueous solution of nitric acid is used, the concentration of nitric acid is preferably 1.0 to 40.0 mass%. The concentration of nitric acid is more preferably 5.0 mass% or more. The concentration of nitric acid is more preferably 35.0 mass% or less. Note that the components other than nitric acid in the aqueous solution of nitric acid are basically water, although unavoidable impurities may be included.
[0062] Processing temperature (temperature of processing solution): 30 to 60°C From the viewpoint of effectively removing the above smut, the treatment temperature is set to 30 to 60° C. The treatment temperature is preferably 45° C. or higher.
[0063] Processing time: 5 to 120 seconds The longer the treatment time, the more the removal of smut is promoted, but if the treatment time is too long, the effect becomes saturated and the productivity decreases. Therefore, the treatment time is set to 5 to 120 seconds. The treatment time is preferably 30 seconds or more. The treatment time is preferably 90 seconds or less.
[0064] During the second surface treatment, if necessary, rubbing the surface of the stainless steel plate to be treated with a nonwoven fabric wiper or the like will make it easier to remove smut, thereby achieving a further stable reduction in contact resistance.
[0065] [Preliminary surface treatment (preliminary smut removal treatment)] Optionally, a preliminary surface treatment for preliminary smut removal may be performed after the first surface treatment step and before the second surface treatment step. The preliminary surface treatment reduces the amount of smut adhesion before the second surface treatment step, and suppresses deterioration of the solution used in the second surface treatment step. As a result, the efficiency of the second surface treatment step can be improved. Examples of treatment solutions used in the preliminary surface treatment include an acidic aqueous solution containing hydrogen peroxide and an acid, and an acidic aqueous solution containing hydrogen peroxide and an acid and / or a persulfate.
[0066] Here, the acidic aqueous solution containing hydrogen peroxide and an acid includes a mixed aqueous solution of hydrogen peroxide and sulfuric acid. When using the mixed aqueous solution, the hydrogen peroxide concentration is preferably 0.5 to 10.0% by mass, and the sulfuric acid concentration is preferably 1.0 to 10.0% by mass. As the acid, hydrochloric acid or nitric acid can be used in addition to sulfuric acid. If necessary, the mixed aqueous solution may contain 0.5 to 2.5% by mass of alcohol such as methanol, ethanol, or n-propanol. The components of the mixed aqueous solution other than hydrogen peroxide, sulfuric acid, and alcohol are basically water, although unavoidable impurities may be contained.
[0067] Examples of the acidic aqueous solution containing hydrogen peroxide, an acid, and / or a persulfate include a mixed aqueous solution of hydrogen peroxide, sulfuric acid, hydrochloric acid, nitric acid, and / or sodium persulfate, potassium persulfate, and ammonium persulfate. When using the mixed aqueous solution, the hydrogen peroxide concentration is preferably 0.5 to 10.0% by mass, the acid concentration is preferably 0 to 10.0% by mass, and the persulfate concentration is preferably 0 to 20.0% by mass. The components of the mixed aqueous solution other than the hydrogen peroxide, acid, and persulfate may contain unavoidable impurities, but are basically water. If necessary, the mixed aqueous solution may contain 0.5 to 2.5% by mass of alcohol such as methanol, ethanol, and n-propanol. The components of the mixed aqueous solution other than the persulfuric acid and alcohol may contain unavoidable impurities, but are basically water.
[0068] The conditions for the preliminary surface treatment are not particularly limited and may be those of a conventional method. For example, the treatment temperature (temperature of the treatment liquid) and treatment time are preferably 30 to 60°C and 5 to 120 seconds, regardless of which of the above treatment liquids is used. The treatment time is more preferably 30 seconds or more. The treatment time is more preferably 90 seconds or less.
[0069] [others] A surface treatment film may be further formed on the surface of the stainless steel sheet obtained after the second surface treatment. The surface treatment film to be formed is not particularly limited, but it is preferable to use a material that has excellent corrosion resistance and electrical conductivity in the usage environment of the fuel cell separator, and for example, it is preferable to use a metal layer, an alloy layer, a metal oxide layer, a metal carbide layer, a metal nitride layer, a carbon material layer, a conductive polymer layer, an organic resin layer containing a conductive substance, or a mixture layer of these.
[0070] For example, the metal layer may be a metal layer of Au, Ag, Cu, Pt, Pd, W, Sn, Ti, Al, Zr, Nb, Ta, Ru, Ir, or Ni, and among these, a metal layer of Au or Pt is preferable. Examples of alloy layers include Sn alloy layers such as Ni-Sn (Ni3Sn2, Ni3Sn4), Cu-Sn (Cu3Sn, Cu6Sn5), Fe-Sn (FeSn, FeSn2), Sn-Ag, and Sn-Co, as well as alloy layers such as Ni-W, Ni-Cr, and Ti-Ta, with Ni-Sn and Fe-Sn alloy layers being particularly preferred. Furthermore, examples of the metal oxide layer include metal oxide layers such as SnO2, ZrO2, TiO2, WO3, SiO2, Al2O3, Nb2O5, IrO2, RuO2, PdO2, Ta2O5, Mo2O5, and Cr2O3, and among these, metal oxide layers of TiO2 and SnO2 are preferable. In addition, examples of the metal nitride layer and metal carbide layer include metal nitride layers and metal carbide layers such as TiN, CrN, TiCN, TiAlN, AlCrN, TiC, WC, SiC, B4C, molybdenum nitride, CrC, TaC, and ZrN, and among these, a metal nitride layer of TiN is preferable. Examples of the carbon material layer include layers of carbon materials such as graphite, amorphous carbon, diamond-like carbon, carbon black, fullerene, and carbon nanotubes, and among these, layers of graphite and diamond-like carbon are preferable. Further examples of the conductive polymer layer include conductive polymer layers such as polyaniline and polypyrrole. In addition, the organic resin layer containing a conductive substance contains at least one conductive substance selected from the metals and alloys, metal oxides, metal nitrides, metal carbides, carbon materials, and conductive polymers constituting the above-mentioned metal layer, alloy layer, metal oxide layer, metal nitride layer, metal carbide layer, carbon material layer, and conductive polymer layer, and contains at least one organic resin selected from epoxy resins, phenolic resins, polyamideimide resins, polyester resins, polyphenylene sulfide resins, polyamide resins, urethane resins, acrylic resins, polyethylene resins, polypropylene resins, carbodiimide resins, and phenolic epoxy resins, etc. As an organic resin layer containing such a conductive substance, for example, a phenolic resin in which graphite is dispersed, or an epoxy resin in which carbon black is dispersed, etc. are suitable. As the conductive material, metals and carbon materials (particularly graphite and carbon black) are suitable. The content of the conductive material is not particularly limited as long as a predetermined conductivity in the separator for the polymer electrolyte fuel cell is obtained. Moreover, the above-mentioned mixture layer may be, for example, a mixture layer of a Ni-Sn alloy in which TiN is dispersed. The above treatment may also be carried out after the stainless steel plate has been worked into the shape of a separator.
[0071] (2) Stainless steel sheets for fuel cell separators Next, we will explain the stainless steel plate for fuel cell separators (hereinafter simply referred to as stainless steel plate for fuel cell separators) manufactured by the manufacturing method for stainless steel plate for fuel cell separators according to one embodiment of the present invention described above.
[0072] Parameter Sa specified in ISO 25178: 0.15 μm to 0.50 μm Sa is a type of surface roughness parameter defined in ISO 25178, and represents the arithmetic mean height. The arithmetic mean height is the average of the absolute values of the differences in height of each point relative to the average plane of the surface, and is a parameter that is generally used when evaluating surface roughness. As described above, in a stainless steel sheet for a separator of a fuel cell, when the separator (stainless steel sheet) and the gas diffusion layer come into contact with each other, the tips of the convex parts formed on the surface of the stainless steel sheet pierce the carbon fibers of the gas diffusion layer. Then, the part (the part where the tips of the convex parts pierce the carbon fibers of the gas diffusion layer) becomes a current path, and the contact resistance is reduced. For this purpose, in addition to the tips of the convex parts being sharp, it is necessary that the tips of the convex parts pierce the carbon fibers of the gas diffusion layer sufficiently. Therefore, Sa is set to 0.15 μm or more. Sa is preferably 0.20 μm or more. However, if Sa exceeds 0.50 μm, the thickness of the stainless steel sheet for a separator of a fuel cell becomes non-uniform due to the etching process. That is, the etching progresses locally, the sheet becomes thinner, and the sheet becomes more likely to break. Therefore, Sa is set to 0.50 μm or less. Sa is preferably 0.48 μm or less, more preferably 0.45 μm or less, and further preferably 0.40 μm or less.
[0073] Parameter Ssk (skewness) specified in ISO 25178: 0 or more The parameter Ssk (skewness) defined in ISO 25178 is a type of surface roughness parameter and indicates the symmetry of the height distribution. As shown in FIG. 2, when Ssk (skewness) is a positive value (greater than 0), it indicates that the tip (upper end) of the convex part (peak) becomes sharp and the tip (lower end) of the concave part (valley) becomes wide (approaching flat). On the other hand, when Ssk is a negative value (less than 0), it indicates that the tip (upper end) of the convex part (peak) becomes wide (approaching flat) and the tip (lower end) of the concave part (valley) becomes sharp. As described above, in a stainless steel plate for a separator of a fuel cell, when the separator (stainless steel plate) and the gas diffusion layer come into contact with each other, the tip of the convex part formed on the surface of the stainless steel plate pierces the carbon fiber of the gas diffusion layer. Then, the part (the part where the tip of the convex part pierces the carbon fiber of the gas diffusion layer) becomes a current path, and the contact resistance is reduced. Therefore, it is necessary that the tips of the projections formed on the surface of the stainless steel plate for fuel cell separators are sharp. Therefore, Ssk is set to be greater than 0. Ssk is preferably 0.10 or more. There is no particular upper limit for Ssk, but if it is increased too much, the number of projections may decrease, which may increase the contact resistance instead, so Ssk is preferably set to 1.0 or less.
[0074] Sa and Ssk may be measured in accordance with ISO 25178. A laser microscope may be used as the measuring device. In the case of a stainless steel sheet for a fuel cell separator, it is sufficient that Sa is 0.15 μm or more and 0.50 μm or less and Ssk is more than 0 on at least one surface (the surface in contact with the gas diffusion layer).
[0075] [Other than metal form (Cr+Fe)] / [metal form (Cr+Fe)]: 8.0 or less As described above, by controlling the ratio of [non-metallic form (Cr+Fe)] / [metallic form (Cr+Fe)] to 8.0 or less, the effect of reducing the contact resistance in the fuel cell separator usage environment can be further improved. Therefore, the ratio of [non-metallic form (Cr+Fe)] / [metallic form (Cr+Fe)] is set to 8.0 or less. The ratio of [non-metallic form (Cr+Fe)] / [metallic form (Cr+Fe)] is more preferably 7.0 or less, even more preferably 6.0 or less, and even more preferably 5.0 or less. If the ratio of [non-metallic form (Cr+Fe)] / [metallic form (Cr+Fe)] exceeds 8.0, the removal of smut from the steel sheet surface cannot be said to be sufficient, and further reduction of the contact resistance cannot be achieved. Although the lower limit of the ratio of [non-metallic form (Cr+Fe)] / [metallic form (Cr+Fe)] is not particularly limited, if an attempt is made to reduce it excessively, the treatment time will be long, so the ratio of [non-metallic form (Cr+Fe)] / [metallic form (Cr+Fe)] is preferably set to 2.0 or more. The non-metallic form refers to the form of oxide and hydroxide. Specifically, in the case of Cr, examples include CrO2, Cr2O3, CrOOH, Cr(OH)3, and CrO3. In the case of Fe, examples include FeO, Fe3O4, Fe2O3, and FeOOH.
[0076] Here, [Other than metallic form (Cr+Fe)] / [Metallic form (Cr+Fe)] is calculated as follows. That is, the surface of a stainless steel plate for a fuel cell separator is measured by X-ray photoelectron spectroscopy (hereinafter also referred to as XPS), and the obtained Cr peak is separated into a peak of Cr existing in a metallic form and a peak of Cr existing in a non-metallic form. Similarly, the obtained Fe peak is separated into a peak of Fe existing in a metallic form and a peak of Fe existing in a non-metallic form. The sum of the atomic concentrations of Cr existing in a non-metallic form and Fe existing in a non-metallic form calculated from the above is divided by the sum of the atomic concentrations of Cr existing in a metallic form and Fe existing in a metallic form to obtain [non-metallic form (Cr+Fe)] / [metallic form (Cr+Fe)]. Specifically, a 10 mm square sample is cut out from the steel plate, and this sample is measured using an X-ray photoelectron spectrometer (X-tool manufactured by ULVAC-PHI, Inc.) with an Al-Kα monochromatic X-ray source and a take-off angle of 45 degrees. Next, the Cr and Fe peaks obtained by the measurement are separated into a peak of Cr and Fe existing in a metallic form and a peak of Cr and Fe existing in a non-metallic form, respectively. Next, the sum of the atomic concentrations of Cr present in a form other than metal and Fe present in a form other than metal calculated from the above is divided by the sum of the atomic concentrations of Cr present in a metallic form and Fe present in a metallic form to obtain [non-metallic form (Cr+Fe)] / [metallic form (Cr+Fe)]. Note that peak separation is performed by removing the spectral background using the Shirley method and using a Gauss-Lorentz composite function (proportion of Lorentz function: 30%).
[0077] The composition of the stainless steel sheet for fuel cell separators is not particularly limited, but preferably contains, by mass%, C: 0.100% or less, Si: 2.00% or less, Mn: 3.00% or less, P: 0.050% or less, S: 0.010% or less, Cr: 15.0 to 25.0%, Ni: 0.01 to 30.0%, Al: 0.500% or less, and N: 0.100% or less, Optionally, (a) Cu: 2.50% or less, (b) Mo: 4.00% or less, and (c) One or more elements selected from Ti, Nb, and Zr: 1.00% or less in total; Contains one or more selected from the following: It is preferable that the balance be Fe and unavoidable impurities (hereinafter, also referred to as a preferable composition). The reasons for this are explained below. Note that "%" in the composition of a component means % by mass unless otherwise specified.
[0078] C: 0.100% or less C reacts with Cr in the steel and precipitates as Cr carbide at the grain boundary. Therefore, C reduces corrosion resistance. From the viewpoint of corrosion resistance, therefore, the less C, the better, and the C content is preferably 0.100% or less. The C content is more preferably 0.060% or less. The lower limit of the C content is not particularly limited, but it is preferably 0.001%.
[0079] Si:2.00% or less Silicon is an effective element for deoxidization and is added at the steel smelting stage. This effect is preferably obtained with a silicon content of 0.01% or more. However, excessive silicon content tends to harden the steel and reduce ductility. Therefore, the silicon content is preferably 2.00% or less. The silicon content is more preferably 1.00% or less.
[0080] Mn:3.00% or less Mn is an effective element for deoxidization and is added at the steel smelting stage. This effect is preferably obtained with a Mn content of 0.01% or more. However, if the Mn content exceeds 3.00%, the corrosion resistance is likely to decrease. Therefore, the Mn content is preferably 3.00% or less. The Mn content is more preferably 1.50% or less, and further preferably 1.00% or less.
[0081] P:0.050% or less Since P reduces ductility, a small content is desirable. However, if the P content is 0.050% or less, there is no significant reduction in ductility. Therefore, the P content is preferably 0.050% or less. The P content is more preferably 0.040% or less. There is no particular limit on the lower limit of the P content, but excessive de-P leads to increased costs. Therefore, the P content is preferably 0.010% or more.
[0082] S: 0.010% or less S is an element that bonds with Mn to form MnS, thereby reducing corrosion resistance. However, if the S content is 0.010% or less, there is no significant reduction in corrosion resistance. Therefore, the S content is preferably 0.010% or less. There is no particular limit on the lower limit of the S content, but excessive de-S leads to increased costs. Therefore, the S content is preferably 0.001% or more.
[0083] Cr: 15.0~25.0% In order to ensure corrosion resistance, the Cr content is preferably 15.0% or more. That is, if the Cr content is less than 15.0%, it becomes difficult to withstand long-term use as a separator for a fuel cell in terms of corrosion resistance. The Cr content is more preferably 18.0% or more. On the other hand, if the Cr content exceeds 25.0%, a sufficient amount of etching may not be obtained. Therefore, the Cr content is preferably 25.0% or less. The Cr content is more preferably 23.0% or less, and further preferably 21.0% or less.
[0084] Ni: 0.01 to 30.0% Ni is an element effective in improving the corrosion resistance of stainless steel. A certain amount of Ni is usually contained in austenitic stainless steel and ferritic-austenitic duplex stainless steel. However, if the Ni content exceeds 30.0%, the hot workability decreases. Therefore, the Ni content is preferably 30.0% or less. The Ni content is more preferably 20.0% or less. The Ni content is preferably 0.01% or more.
[0085] The preferred lower limit of the Ni content in austenitic stainless steel and ferritic-austenitic duplex stainless steel is 2.00%. When Ni is contained in ferritic stainless steel, the Ni content is preferably 2.00% or less, more preferably 1.00% or less. The preferred lower limit of the Ni content in ferritic stainless steel is 0.01%.
[0086] Al: 0.500% or less Al is an element used for deoxidation. This effect is preferably obtained with an Al content of 0.001% or more. However, if the Al content exceeds 0.500%, it may cause a decrease in ductility. Therefore, the Al content is preferably 0.500% or less. The Al content is more preferably 0.010% or less, and further preferably 0.005% or less.
[0087] N: 0.100% or less If the N content exceeds 0.100%, the formability decreases. Therefore, the N content is preferably 0.100% or less. The N content is more preferably 0.050% or less, and further preferably 0.030% or less. There is no particular limit to the lower limit of the N content, but excessive denitrification leads to increased costs. Therefore, the N content is preferably 0.002% or more.
[0088] In addition to the above components, the following components may also be contained. Cu:2.50% or less Cu is an element that is effective in promoting the formation of the austenite phase and improving the corrosion resistance of stainless steel. This effect is preferably obtained with a Cu content of 0.01% or more. However, if the Cu content exceeds 2.50%, hot workability is reduced, leading to a decrease in productivity. Therefore, when Cu is contained, the Cu content is set to 2.50% or less. The Cu content is preferably 1.00% or less.
[0089] Mo: 4.00% or less Mo is an element effective in suppressing local corrosion such as crevice corrosion of stainless steel. This effect is preferably obtained with a Mo content of 0.01% or more. However, if the Mo content exceeds 4.00%, it leads to embrittlement of the stainless steel. Therefore, when Mo is contained, the Mo content is set to 4.00% or less. The Mo content is preferably 2.50% or less.
[0090] One or more elements selected from Ti, Nb and Zr: 1.00% or less in total Ti, Nb and Zr contribute to improving intergranular corrosion resistance, so these elements can be contained alone or in combination. The effect is preferably obtained when each of them is contained at 0.01% or more. However, if the total content of these elements exceeds 1.00%, ductility is likely to decrease. Therefore, when Ti, Nb and Zr are contained, the total content of these elements is set to 1.00% or less. There is no particular limit on the lower limit of the total content of Ti, Nb and Zr, but it is preferable that the total content of Ti, Nb and Zr is set to 0.01% or more.
[0091] The components other than those mentioned above are Fe and unavoidable impurities.
[0092] In the final product of the stainless steel sheet for fuel cell separators, the structure and average grain size of the stainless steel sheet material are basically maintained, so a description thereof will be omitted here. In addition, the surface of the stainless steel sheet for fuel cell separators may further have the above-mentioned surface treatment film.
[0093] In addition, in consideration of the mounting space and weight when stacking the fuel cells, the plate thickness of the stainless steel plate for the fuel cell separator is preferably in the range of 0.03 to 0.30 mm. If the plate thickness is less than 0.03 mm, the production efficiency of the metal plate material decreases. On the other hand, if the plate thickness exceeds 0.30 mm, the mounting space and weight when stacking increase. The plate thickness of the stainless steel plate for the fuel cell separator is more preferably 0.05 mm or more. Furthermore, the plate thickness of the stainless steel plate for the fuel cell separator is more preferably 0.15 mm or less. EXAMPLES
[0094] Example 1 A stainless steel sheet having a thickness of 0.10 mm (0.10 mm×60 mm×40 mm) and having the composition of steel Nos. A to G shown in Table 1 (the balance being Fe and unavoidable impurities) was prepared (bright annealed after cold rolling). The prepared stainless steel sheet was then subjected to a first surface treatment (etching treatment) and a second surface treatment (smut removal treatment) under the conditions shown in Table 2 to obtain a stainless steel sheet for a separator of a fuel cell. In some samples, a preliminary surface treatment (preliminary smut removal treatment) was performed after the first surface treatment and before the second surface treatment. The first surface treatment, the second surface treatment, and the preliminary surface treatment were all performed by immersion treatment in which the stainless steel sheet was immersed in each treatment solution. After the second surface treatment, the stainless steel sheet was immersed in pure water to stop the reaction. First surface treatment solution A1 Hydrogen peroxide: 0.2% by mass Copper ions: 1.5% by mass Chloride ions: 10.0% by mass Remainder: water pH: 0.05 The copper ions and chloride ions are derived from copper sulfate pentahydrate and hydrochloric acid, respectively. First surface treatment solution A2 Hydrogen peroxide: 0.3% by mass Copper ions: 2.0% by mass Chloride ions: 15.0% by mass Remainder: water pH: 0.05 The copper ions and chloride ions are derived from copper sulfate pentahydrate and hydrochloric acid, respectively. ·First surface treatment solution A3 Hydrogen peroxide: 0.3% by mass Copper ions: 9.0% by mass Chloride ions: 10.0% by mass Remainder: water pH: 0.05 The copper ions and chloride ions are derived from copper sulfate pentahydrate and hydrochloric acid, respectively. · First surface treatment solution A4 Hydrogen peroxide: 2.0% by mass Copper ions: 2.0% by mass Chloride ions: 10.0% by mass Remainder: water pH: 0.05 The copper ions and chloride ions are derived from copper sulfate pentahydrate and hydrochloric acid, respectively. ·Preliminary surface treatment solution B1 Hydrogen peroxide: 3.0% by mass Sulfuric acid: 6.0% by mass Remainder: water ·Preliminary surface treatment solution B2 Hydrogen peroxide: 2.0% by mass Sulfuric acid: 4.0% by mass Remainder: water · Second surface treatment solution N1 Nitric acid: 30.0% by mass Remainder: water · Second surface treatment solution N2 Nitric acid: 20.0% by mass Remainder: water · Second surface treatment solution N3 Nitric acid: 8.0% by mass Remainder: water Second surface treatment solution C1 (for comparison) Hydrochloric acid: 10.0% by mass Remainder: water
[0095] The thus obtained stainless steel plate for fuel cell separator was measured for Sa and Ssk in accordance with ISO 25178. A laser microscope (Keyence VK-X250 / X260) was used for the measurement. Specifically, a test piece was taken from the stainless steel plate for fuel cell separator, and the surface shape data of a 50 μm × 50 μm area on both sides of the test piece was measured by the above-mentioned laser microscope using an objective lens with a magnification of 150 times. The obtained data was analyzed by the analysis software "Multi-file analysis application" attached to the device, and Sa and Ssk were obtained on both sides of the test piece. Before analyzing Sa and Ssk, image processing was performed by removing and interpolating the part where the light amount was outside the threshold range (0.00 to 99.5), and noise was removed by smoothing using a Gaussian function and setting a cut level. Then, a plane serving as a reference for measurement was set by setting a reference plane, and the curved surface was corrected to a flat surface by quadratic curve correction. The filter type was Gaussian, and the cutoff wavelength specified by the S-filter was 0.5 μm. The measurement results are shown in Table 2. Note that the values of Sa and Ssk were almost the same on both sides of each test piece, so in Table 2, the values of Sa and Ssk measured on one side of the test piece are shown as representative values. For reference, the steel plate No. B in Table 1 was used as a stainless steel plate, and 10 mass% sulfuric acid was used to measure -1 mA / cm 2 ×90 sec, and +0.03mA / cm 2 The steel sheet was subjected to electrolytic treatment under the condition of 2000 s × 90 seconds, and the values of Sa and Ssk of the steel sheet after treatment were measured. The results were Sa was 0.14 μm and Ssk was 0.90.
[0096] In addition, the ratio of [Cr+Fe other than metal form] / [Cr+Fe metal form] was calculated using the method described above. The results are shown in Table 2.
[0097] The composition of the resulting stainless steel sheets for fuel cell separators was substantially the same as that of the respective steel Nos. listed in Table 1, and all of the sheets satisfied the above-mentioned range of the preferred composition. Furthermore, the structure of the prepared stainless steel sheet material was maintained in all of the resulting stainless steel sheets for fuel cell separators.
[0098] In addition, the contact resistance of the obtained stainless steel sheets for fuel cell separators was evaluated in the following manner.
[0099] Contact resistance evaluation A sample of 0.10 mm x 50 mm x 20 mm was cut out from the stainless steel plate for fuel cell separator obtained as described above. The sample was then sandwiched between carbon paper (Toray Industries, Inc., TGP-H-120) and contacted with gold-plated copper electrodes from both sides. A pressure of 0.98 MPa (=10 kg / cm) per unit area was applied. 2 ) pressure was applied to pass a current. The voltage difference between the electrodes was then measured to calculate the electrical resistance. This electrical resistance measurement was then multiplied by the area of the contact surface, divided by 2, and the internal resistance of the carbon paper (3 mΩ cm 2 ) is subtracted from the contact resistance value ([Contact resistance value (mΩ cm 2 )] = {[Measured electrical resistance (mΩ)] × [Contact surface area (cm 2 The contact resistance was evaluated according to the following criteria. The evaluation results are shown in Table 2. ◎ (Pass (particularly excellent)): 5.0mΩ·cm 2 below ○(Pass): 5.0mΩ·cm 2 Super 10.0mΩ·cm 2 below ×(Fail):10.0mΩ·cm 2 super
[0100] - Evaluation of corrosion resistance (stability in the separator usage environment) A sample of 0.10 mm×50 mm×20 mm was cut out from the stainless steel plate for the separator of the fuel cell obtained as described above. The test area of the sample was 40 mm×20 mm, and the remaining part was sealed with resin. Next, the sample was immersed in a sulfuric acid aqueous solution containing 0.1 mass ppm of hydrofluoric acid at pH: 3.0 and temperature: 80° C. Then, the sample was held in the sulfuric acid aqueous solution for 25 hours at a potential of 0.6 V simulating the separator use environment, and the current density value after 25 hours was measured. Note that Ag / AgCl (saturated KCl) was used as the reference electrode. Then, the corrosion resistance (stability in the separator use environment) after 25 hours in the separator use environment was evaluated according to the measured current density value after 25 hours, based on the following criteria. The evaluation results are also shown in Table 2. ○(Pass):1.0μA / cm 2 below ×(Fail):1.0μA / cm 2 super
[0101] [Table 1]
[0102] [Table 2]
[0103] From Table 2, the following points are clear: (a) In all of the inventive samples No. 1 to No. 17, the desired low contact resistance was obtained. In addition, good corrosion resistance (stability in the separator usage environment) was also obtained. (b) On the other hand, the desired low contact resistance was not obtained in Comparative Example No. 18. In Comparative Examples No. 19 and No. 20, a significant amount of smut was found to adhere, and Sa, Ssk, and [Cr+Fe other than metal form] / [Cr+Fe metal form] could not be measured. Therefore, evaluation of contact resistance and corrosion resistance (stability in the separator usage environment) were not performed.
[0104] Example 2 For the steel symbols B and H in Table 1, cold-rolled stainless steel sheets with a thickness of 0.10 mm (0.10 mm x 300 mm x 200 mm) were prepared. In addition, after hot rolling and cold rolling, some of the stainless steel sheets were further finish-annealed (cold-rolled sheet annealing) under the conditions shown in Table 3 in a mixed atmosphere of H2 and N2 (volume ratio of H2:N2 = 75:25, dew point: -50°C).
[0105] Next, the average grain size of the prepared stainless steel sheets was measured in the manner described above. The measurement results are shown in Table 3. "Not measurable" in the average grain size column of Table 3 means that no grain boundaries were observed in the EBSD (electron backscatter diffraction) analysis, and the average grain size could not be measured. The sheet thickness of these stainless steel sheets was also measured at the center of the test pieces with a micrometer.
[0106] Next, a first surface treatment (etching treatment) and a second surface treatment (smut removal treatment) were performed under the conditions shown in Table 3 to obtain a stainless steel sheet for a fuel cell separator. Note that the treatment solutions A1 and N1 in Table 3 were the same as those used in Example 1. After the second surface treatment, the stainless steel sheet was immersed in pure water to stop the reaction.
[0107] The thickness of the thus obtained stainless steel sheet for fuel cell separator was measured with a micrometer, and the thickness of the stainless steel sheet for fuel cell separator measured after surface treatment was subtracted from the thickness of the material stainless steel sheet measured before surface treatment to calculate the thickness reduction of the material stainless steel sheet. Sa and Ssk were measured in the same manner as in Example 1. Furthermore, [Other than metal form (Cr+Fe)] / [Metal form (Cr+Fe)] was calculated in the same manner as in Example 1. The results are also shown in Table 3. The composition of the obtained stainless steel sheet for fuel cell separator was substantially the same as the composition of each steel No. listed in Table 1, and all of them satisfied the above-mentioned range of the preferable composition. In addition, the structure and average grain size of the prepared material stainless steel sheet were maintained in all of the obtained stainless steel sheets for fuel cell separator.
[0108] In addition, the stainless steel sheets for fuel cell separators were evaluated for (1) contact resistance and (2) corrosion resistance in the same manner as in Example 1. The evaluation results are shown in Table 3.
[0109] [Table 3]
[0110] As shown in Table 3, the desired low contact resistance was obtained in all of the inventive examples, and good corrosion resistance was also obtained. In particular, in samples Nos. 2-3, 2-4, 2-5, 2-6, 2-9, 2-10, 2-11 and 2-12, in which the average crystal grain size of the prepared stainless steel plate was 10 μm or more and 40 μm or less, particularly low contact resistance was obtained while reducing the amount of dissolution of the stainless steel plate in the first surface treatment.
Claims
1. A method for producing a stainless steel sheet for a separator of a fuel cell, which produces a stainless steel sheet for a separator of a fuel cell that simultaneously satisfies the following (a) to (c): The production method comprises the steps of: a first surface treatment step of subjecting a base stainless steel sheet to a first surface treatment; a second surface treatment step of subjecting the base stainless steel plate to a second surface treatment after the first surface treatment step; In the first surface treatment, The treatment liquid is an acidic aqueous solution containing 0.1 to 5.0 mass % hydrogen peroxide, 1.0 to 10.0 mass % copper ions, and 5.0 to 20.0 mass % chloride ions and having a pH of 1.0 or less; and Processing temperature: 30 to 50°C and Processing time: 40 to 120 seconds and In the second surface treatment, The treatment liquid is an aqueous solution containing nitric acid, Processing temperature: 30 to 60°C and Processing time: 5 to 120 seconds This is a method for manufacturing stainless steel sheets for fuel cell separators. (a) Parameter Sa defined in ISO 25178: 0.15 μm or more and 0.50 μm or less (b) Parameter Ssk defined in ISO 25178: greater than 0 (c) [Other than metal form (Cr+Fe)] / [Metal form (Cr+Fe)]: 8.0 or less Here, [non-metallic form (Cr+Fe)] / [metallic form (Cr+Fe)] is the ratio of the sum of Cr and Fe present in a non-metallic form to the sum of Cr and Fe present in a metallic form on the steel sheet surface. Also, [metallic form (Cr+Fe)] and [non-metallic form (Cr+Fe)] are the sum of the atomic concentrations of Cr and Fe present in a metallic form and the sum of the atomic concentrations of Cr and Fe present in a non-metallic form, respectively, measured when the steel sheet surface is analyzed by X-ray photoelectron spectroscopy.
2. 2. The method for producing a stainless steel plate for a fuel cell separator according to claim 1, wherein the average crystal grain size of the base stainless steel plate is 10 μm or more and 40 μm or less.
3. A method for producing a stainless steel sheet for a separator of a fuel cell according to claim 2, comprising the steps of: The method further comprises: a hot rolling step of hot rolling the steel slab into a hot rolled sheet; A cold rolling process in which the hot rolled sheet is cold rolled to obtain a cold rolled sheet; A cold-rolled sheet annealing process for subjecting the cold-rolled sheet to cold-rolled sheet annealing; The base stainless steel plate is an austenitic stainless steel plate, and In the final annealing, which is the final annealing of the cold-rolled sheet annealing, Final annealing temperature: 1050 to 1250°C and Finish annealing time: 20 to 90 seconds This is a method for manufacturing stainless steel sheets for fuel cell separators.
4. A method for producing a stainless steel sheet for a separator of a fuel cell according to claim 2, comprising the steps of: The method further comprises: a hot rolling step of hot rolling the steel slab into a hot rolled sheet; A cold rolling process in which the hot rolled sheet is cold rolled to obtain a cold rolled sheet; A cold-rolled sheet annealing process for subjecting the cold-rolled sheet to cold-rolled sheet annealing; The base stainless steel plate is a ferritic stainless steel plate, and In the final annealing, which is the final annealing of the cold-rolled sheet annealing, Final annealing temperature: 750 to 1050°C and Finish annealing time: 20 to 90 seconds This is a method for manufacturing stainless steel sheets for fuel cell separators.
Citation Information
Patent Citations
Raillfastening device
JP1977018612A
Cooling air circulating electric rotary machine
JP1982068641A
Solid polymer electrolytic fuel cell
JP1996180883A
Stainless cold-rolled steel sheet superior in surface appearance after having been worked, and method for manufacturing the same
JP2011195874A
Method for manufacturing stainless steel for fuel battery separators, stainless steel for fuel battery separators, fuel battery separator, and fuel battery
JP2013093299A